1990
DOI: 10.1055/s-2006-960985
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Compounds Containing an α, β-Unsaturated Carbonyl Moiety from Tanzanian Medicinal Plants1

Abstract: Pure compounds were isolated from plant extracts with antimalarial activity. The extracts were obtained from the tubers of Cyperus rotundus L. (Cyperaceae), the rootbark of Zanthoxylum gilletii (De Wild) Waterm. (Rutaceae), and the rootbark of Margaritaria discoidea (Baill.) Webster (Euphorbiaceae). The most active compounds included (IC50 within brackets): alpha-cyperone (1) (5.5 micrograms/ml), N-isobutyldeca-2,4-dienamide (2) (5.4 micrograms/ml), and securinine (3) (5.4 micrograms/ml). A mixture of autoxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 5 publications
2
75
0
3
Order By: Relevance
“…Achillea, Anacyclus, Artemisia, Leucocyclus, Chamaemelum, Cladanthus, Argyranthemum and Matricaria) (Christensen, 1992). Since then however, those fatty acid moieties are also found in the Heliantheae tribe and other families: Rutaceae, Piperaceae, Aristolochiaceae and Menispermacea (AndradeNeto et al, 1996;Burden and Crombie, 1969;Greger et al, 1981;Greger and Werner, 1990;Saadali et al, 2001;Weenen et al, 1990b;Yasuda et al, 1981a). Nevertheless, the thiophene fatty acid moiety is a typical characteristic of Anthemideae, which was identified in e.g.…”
Section: Q10mentioning
confidence: 99%
See 1 more Smart Citation
“…Achillea, Anacyclus, Artemisia, Leucocyclus, Chamaemelum, Cladanthus, Argyranthemum and Matricaria) (Christensen, 1992). Since then however, those fatty acid moieties are also found in the Heliantheae tribe and other families: Rutaceae, Piperaceae, Aristolochiaceae and Menispermacea (AndradeNeto et al, 1996;Burden and Crombie, 1969;Greger et al, 1981;Greger and Werner, 1990;Saadali et al, 2001;Weenen et al, 1990b;Yasuda et al, 1981a). Nevertheless, the thiophene fatty acid moiety is a typical characteristic of Anthemideae, which was identified in e.g.…”
Section: Q10mentioning
confidence: 99%
“…From different studies, it was suggested that the a,b-unsaturated carbonyl function rather than the N-isobutyl substituent is the responsible active site (Penali et al, 2007;Sittie et al, 1998;Weenen et al, 1990a). Longer, straight chain acid moieties and substituted (rather than primary) amines seem advantageous.…”
Section: Antimicrobial and Related Activitiesmentioning
confidence: 99%
“…Espécies do gênero Zanthoxylum são utilizadas na medicina popular no tratamento de doenças cardiovasculares, tuberculose, malária, para aliviar dor de dente, contra mordida de cobra e como analgésico (Weenen et al, 1990;Arruda et al, 1992;Gessler et al, 1994;Vigneron et al, 2005). Investigações fi toquímicas identifi caram alcalóides, fl avonóides, cumarinas, lignanas e terpenos no gênero (Talapatra et al, 1973;Stermitz;Sharifi , 1977;Diehl et al, 2000;Oliveira et al, 2002;Facundo et al, 2005;Tane et al, 2005).…”
Section: Introductionunclassified
“…Investigações fitoquímicas anteriores de espécies deste gênero revelaram a presença de alcalóides, flavonóides, cumarinas, lignanas e terpenos [2][3][4][5] . Vá-rias destas espécies são utilizadas na medicina popular no tratamento de doenças cardiovasculares, tuberculose, malária, para aliviar dor de dente e contra mordida de cobra [6][7][8][9] . O estudo fitoquímico de duas espécies comuns do nordeste do Brasil, Z. syncarpum e Z. rugosum, conduziu ao isolamento dos metabólitos secundários skimianina, cis-N-metilcanadina, isopimpinelina, xantotoxina, lupeol, ácido centipédico, 3β-O-β-D-glucopiranosil-sitosterol, 6-cantinona, 6,7-dimetoxicumarina, 6,7,8-trimetoxicumarina, avicenina, hesperidina, ácido 3-(9H-β-carbolina-1-il)-(Z)-2-propenóico e 2-hidróxi-2-(4-hidroxifenil)etil (trimetil) amônio 10,11 .…”
Section: Introductionunclassified